Idiopathic Recurring Angioedema: A Possible Case of Hereditary Angioedema Type III - Sales Biermann, Lara (2018)
Three types of hereditary angioedema (HAE) have been described within the spectrum of idioptahic nonhistaminergic angioedema. Type I and II related with C1-INH (C1-esterase inhibitor) deficiency is more frequent and type III is rare, occurs mostly in young women, without C1 inhibitor (C1-INH) alterations, and may be associated with mutations in the factor XII gene. Trauma, stress and estrogen may be the precipitants, treatment is still a challenge due to the absence of controlled studies. We present a case of possible type III HF in a young woman, aggravated by the introduction of anti-conception and improvement with its suspension and treatment with tranexamic acid, but without a family history or a factor XII mutation.